1989
DOI: 10.1152/jappl.1989.66.2.929
|View full text |Cite
|
Sign up to set email alerts
|

Role of venoconstriction in thromboxane-induced pulmonary hypertension and edema in lambs

Abstract: We evaluated the dose response to a stable thromboxane (Tx) A2 analogue (sTxA2; 0.3-30 micrograms) in the pulmonary circulation and its effect on the distribution of pressure gradients determined by the occlusion technique in isolated nonblood perfused newborn lamb lungs. The total pulmonary pressure gradient (delta Pt) was partitioned into pressure drops across the relatively indistensible arteries and veins (delta Pv) and relatively compliant vessels. We also evaluated the effects of prostacyclin (PGI2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 0 publications
2
32
2
Order By: Relevance
“…TNF release cannot explain all the pathophysiologic effects previously demonstrated in neonatal piglet models of GBS sepsis ( 5 , 6). Thromboxane has been demonstrated to be a pulmonary venoconstrictor and an inducer of pulmonary edema (40). Widespread alveolar pulmonary edema would be expected to interfere with gas exchange, which was not found in these studies.…”
Section: Discussionmentioning
confidence: 65%
“…TNF release cannot explain all the pathophysiologic effects previously demonstrated in neonatal piglet models of GBS sepsis ( 5 , 6). Thromboxane has been demonstrated to be a pulmonary venoconstrictor and an inducer of pulmonary edema (40). Widespread alveolar pulmonary edema would be expected to interfere with gas exchange, which was not found in these studies.…”
Section: Discussionmentioning
confidence: 65%
“…3 Briefly, 23 newborn lambs of either sex, 0-4 days of age and weighing between 2.1 and 5.5 kg, were anesthetized with ketamine hydrochloride (50 mg/kg i.m. ), and a catheter was placed in a femoral artery.…”
Section: Isolated Lung Preparationmentioning
confidence: 99%
“…U-46619 (7.1 ϫ 10 Ϫ8 M) was then added to perfusate, and 15 min later Ppa, Ppv, and Pc were measured, and K f and RT were calculated. 5,37,38). This concentration has been previously shown to inhibit the release of TxA 2 , PGF 2␣ , and PGI 2 in an experimental model similar to that employed in these experiments (3,5).…”
Section: Experimental Protocolmentioning
confidence: 87%
“…In the latter two reports (37,38), the investigators, utilizing an ex vivo newborn lamb lung model, found that the K f of lungs exposed to PGI 2 and a TxA 2 -receptor agonist (9,11-epithio-11,12-methanoTxA 2 ) was significantly greater than that of lungs exposed to either PGI 2 or TxA 2 -receptor activation alone. This increase in fluid filtration was accompanied by a reduction in vascular hydrostatic pressure, suggesting that, in addition to a direct effect on microvascular permeability, PGI 2 may have increased pulmonary K f by increasing vascular surface area (37,38). These results are similar to those of the present study in that the K f of lungs exposed to PGI 2 and U-46619 was nearly 70% greater than that of lungs exposed to U-46619 alone (P Ͻ 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation